Comparative stiffness analysis between conventional and IBS construction method - Hashim, Md. Nasir (2006)
Industrialised Building System (IBS) is a system where the components such as beam, columns and floors are produced in the factory with standard sizes and length. These components are then transported to the construction site for assembly to form buildings. The analysis and design of the IBS structures, like any other building analysis is dependent on the loads, sizes of properties structures (columns, beam and floors) and joints restraints. In this study, the continuous steel bars in the conventional construction method is replaced by rectangular hollow sections for the column to column connections and two steel plates for the beam to column connection. The stiffness restraints this type IBS is found to be nearer to conventional reinforced concrete constructions. It also means that during constructions the joint can be left as it is or grouted with the same concrete strength to the columns and beam. The analysis is carried out using Multiframe 4D software.